2005
DOI: 10.1111/j.1365-2516.2005.00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic treatment effects on inhibitor risk: experience in one centre

Abstract: Nowadays, the elective treatment for children with haemophilia is prophylaxis. There is a common consensus that this modality of therapeutic approach is not associated with a higher risk of inhibitor development. We analysed the inhibitor incidence in 50 haemophiliac children and its relationship with mutations, type of clotting factor used and treatment modality. There was a significant correlation between receiving on-demand treatment and an increased incidence of inhibitors, independently of mutations or fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 17 publications
6
53
1
Order By: Relevance
“…This clearly confirmed previous suggestions of a protective effect of prophylactic treatment. 18,22,32,33 Patient characteristics Furthermore, our study confirmed previous reports of an increased risk of inhibitor development in patients with a positive family history of inhibitors [5][6][7] and patients with large deletions, nonsense mutations, or intron 22 inversion in their factor VIII gene. 8,36,37 In addition, in agreement with previous observations, we did not find a relation between breastfeeding and inhibitor development.…”
Section: Regular Prophylaxissupporting
confidence: 87%
See 2 more Smart Citations
“…This clearly confirmed previous suggestions of a protective effect of prophylactic treatment. 18,22,32,33 Patient characteristics Furthermore, our study confirmed previous reports of an increased risk of inhibitor development in patients with a positive family history of inhibitors [5][6][7] and patients with large deletions, nonsense mutations, or intron 22 inversion in their factor VIII gene. 8,36,37 In addition, in agreement with previous observations, we did not find a relation between breastfeeding and inhibitor development.…”
Section: Regular Prophylaxissupporting
confidence: 87%
“…We had data on breastfeeding in 132 patients (36%). Ninety-one patients had been breastfed, for a median of 13 (IQR, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] weeks. The inhibitor risk was similar in patients with and without breastfeeding.…”
Section: Missing Datamentioning
confidence: 99%
See 1 more Smart Citation
“…High-titer inhibitors developed in 66 patients and low-titer inhibitors, in 16 patients. Patients developed inhibitors after a median of 14 exposure days (interquartile range [IQR],[8][9][10][11][12][13][14][15][16][17][18][19] and at a median age of 15 months (IQR, 10-22 months). …”
mentioning
confidence: 99%
“…32 Much discussion has centred on whether the type of concentrate used, either plasma-derived or recombinant, has an impact on inhibitor development, and some researchers have Table 1). 51 ITI faces a number of potential obstacles in practice.…”
Section: Risk Factors For Inhibitor Developmentmentioning
confidence: 99%